Approaching Long Genomic Regions and Large Recombination Rates with msParSm as an Alternative to MaCS. (January 2016) - Montemuiño, Carlos; Espinosa, Antonio; Moure, Juan C.; Vera, Gonzalo; Hernández, Porfidio; Ramos-Onsins, Sebastián
The msParSm application is an evolution of msPar, the parallel version of the coalescent simulation program ms, which removes the limitation for simulating long stretches of DNA sequences with large recombination rates, without compromising the accuracy of the standard coalescence. This work introduces msParSm, describes its significant performance improvements over msPar and its shared memory parallelization details, and shows how it can get better, if not similar, execution times than MaCS. Two case studies with different mutation rates were analyzed, one approximating the human average and the other approximating the Drosophila melanogaster average. Source code is available athttps://github.com/cmontemuino/msparsm .